2018
DOI: 10.1200/jco.2017.76.3839
|View full text |Cite
|
Sign up to set email alerts
|

Improving Male Reproductive Health After Childhood, Adolescent, and Young Adult Cancer: Progress and Future Directions for Survivorship Research

Abstract: Reproductive health is a common concern and often a source of distress for male childhood, adolescent, and young adult cancer survivors. Clinical and epidemiologic research in survivor populations has identified alkylating agent chemotherapy, testicular radiation, and surgery or radiation to the genitourinary organs, lower spine, or the hypothalamic-pituitary region as risk factors for adverse reproductive outcomes, including impaired spermatogenesis, testosterone insufficiency, and sexual dysfunction. Much of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 67 publications
1
57
0
Order By: Relevance
“…It was shown that cyclophosphamide with an equivalent dose > 5 g/m 2 and radiation > 2 Gy may induce impaired spermatogenesis [33, 34]. Impaired spermatogenesis may be reversible or permanent, depending on the combinations of treatment and on the cumulative dose of chemotherapy given.…”
Section: Primary Gonadal Failure In Male Ccs (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that cyclophosphamide with an equivalent dose > 5 g/m 2 and radiation > 2 Gy may induce impaired spermatogenesis [33, 34]. Impaired spermatogenesis may be reversible or permanent, depending on the combinations of treatment and on the cumulative dose of chemotherapy given.…”
Section: Primary Gonadal Failure In Male Ccs (Table 1)mentioning
confidence: 99%
“…Awareness and screening for sexual impairment in postpubertal males at risk is important since sexual health has been shown to be important for overall health and quality of life. Next to CCS with androgen deficiency, awareness of sexual impairment is also important in males who have been treated with surgery or radiation involving the lower spinal cord, prostate, distal colon or rectum, due to disruption of the innervation required for erection and ejaculation [33]. These CCS may be referred to the urology department for specific techniques to improve sexual function.…”
Section: Primary Gonadal Failure In Male Ccs (Table 1)mentioning
confidence: 99%
“…27,28 Surgery and radiation to the pelvis or lumbar spine has reportedly been linked to sexual dysfunction, as a result of hormonal deficiency and emotional distress. 29 Kenney et al 29 reported that 20% of young adult male cancer patients experienced erectile dysfunction subsequent to treatment, and these findings were supported by several other studies revealing that more than half of all survivors presented with ejaculatory dysfunction following treatment. 3,30 These consequential reproductive outcomes, in relation to fatherhood, can have a detrimental effect on a patient's physical and psychological wellbeing, maintaining relationships, and quality of life.…”
mentioning
confidence: 88%
“…It is well-known that treatments for cancer may cause adverse effects on sexual function. Both Kenney et al 20 and Van Dorp et al 21 reviewed the literature regarding reproductive health of male and female survivors. They noted that alkylating agent chemotherapy and gonadal irradiation carried doserelated risks of primary gonadal dysfunction, which affected both sexual function and fertility.…”
Section: Implications For Patient Treatmentmentioning
confidence: 99%
“…Until this change occurs, healthcare professionals should provide information regarding the potential adverse effects of treatments on the reproductive system and sexual function, as well as counselling to the survivors; importantly, survivors interviewed in previous studies indicated they had unmet needs for information, support, and counselling. 20…”
Section: Implications For Patient Treatmentmentioning
confidence: 99%